2007
DOI: 10.11150/kansenshogakuzasshi1970.81.249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hand Hygiene on Feline Calicivirus Inactivation and Removal as Norovirus Surrogate Treated with Antiseptic Hand Rubbing, Wet Wipes, and Functional Water

Abstract: Table 1 Antiseptic drug products for viral inactivation and removal by hand rubbing trial (A to C), wet wipes (D to G), and functional water (H to K)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…It has been commonly employed in studies involving chemical disinfectants (Cannon et al 2006; D’Souza and Su 2010; Doultree et al 1999; Gehrke et al 2004; Hudson et al 2007; Jimemez and Chiang 2006; Kampf et al 2005; Lages et al 2008; Malik et al 2006; Malik and Goyal 2006; Mori et al 2007; Morino et al 2009; Poschetto et al 2007; Sattar et al 2011; Steinmann 2004; Urakami et al 2007; Whitehead and McCue 2010); and processing interventions, like heating (Buckow et al 2008; Butot et al 2009; Cannon et al 2006), freezing or freeze-drying (Butot et al 2008, 2009), irradiation (de Roda Husman et al 2004; Fino and Kniel 2008; Nuanualsuwan et al 2002), marinating/acidification (Cannon et al 2006; Hewitt and Greening 2004), and high pressure processing (Chen et al 2005; Kingsley et al 2002). A decade after FCV first came on the scene, Wobus et al (2006) identified murine norovirus-1 (MNV) as a closer genetic relative of NoV. Now, MNV has become the more commonly used surrogate for chemical disinfection studies (Belliot et al 2008; Cannon et al 2006; D’Souza and Su 2010; Lee et al 2008; Lim et al 2010; Magulski et al 2009; Park et al 2010; Sattar et al 2011); and studies on processing interventions like heating (Baert et al 2008a; Cannon et al 2006; Hewitt et al 2009; Sow et al 2011; Tanner 2009), freezing (Baert et al 2008b), UV irradiation (Jean et al 2011; Park et al 2011), gamma irradiation (Feng et al 2011), electron beam (Sanglay et al 2011), and high pressure processing (Kingsley et al 2007; Lou et al 2011; Tang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has been commonly employed in studies involving chemical disinfectants (Cannon et al 2006; D’Souza and Su 2010; Doultree et al 1999; Gehrke et al 2004; Hudson et al 2007; Jimemez and Chiang 2006; Kampf et al 2005; Lages et al 2008; Malik et al 2006; Malik and Goyal 2006; Mori et al 2007; Morino et al 2009; Poschetto et al 2007; Sattar et al 2011; Steinmann 2004; Urakami et al 2007; Whitehead and McCue 2010); and processing interventions, like heating (Buckow et al 2008; Butot et al 2009; Cannon et al 2006), freezing or freeze-drying (Butot et al 2008, 2009), irradiation (de Roda Husman et al 2004; Fino and Kniel 2008; Nuanualsuwan et al 2002), marinating/acidification (Cannon et al 2006; Hewitt and Greening 2004), and high pressure processing (Chen et al 2005; Kingsley et al 2002). A decade after FCV first came on the scene, Wobus et al (2006) identified murine norovirus-1 (MNV) as a closer genetic relative of NoV. Now, MNV has become the more commonly used surrogate for chemical disinfection studies (Belliot et al 2008; Cannon et al 2006; D’Souza and Su 2010; Lee et al 2008; Lim et al 2010; Magulski et al 2009; Park et al 2010; Sattar et al 2011); and studies on processing interventions like heating (Baert et al 2008a; Cannon et al 2006; Hewitt et al 2009; Sow et al 2011; Tanner 2009), freezing (Baert et al 2008b), UV irradiation (Jean et al 2011; Park et al 2011), gamma irradiation (Feng et al 2011), electron beam (Sanglay et al 2011), and high pressure processing (Kingsley et al 2007; Lou et al 2011; Tang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The current study emphasizes the correct handling and disinfection methods for norovirus vomitus, which are crucial in preventing the outbreak and spread of norovirus. Therefore, we suggest the following procedure for the proper handling of vomitus from norovirus cases ( 33 , 42 , 43 ): (1) Evacuate people around the vomitus, If in a closed space, windows should be opened to improve ventilation and reduce the concentration of virus aerosols in the air, which can help prevent the spread of norovirus. (2) Personnel should wear protective gear for handling vomitus, including a cap, two pairs of gloves, a mask, and shoe covers.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al designed a Vomit Disposal Kit for acute gastroenteritis caused by norovirus [42], which includes protective equipment for vomitus disposal, disinfection agents and disposal tools. The procedure for vomitus disposal is as follows: (1) evacuate people around the vomitus; (2) personnel should wear protective equipment, including a hat, two pairs of gloves, mask, shoe covers, etc., while disinfecting; (3) prepare a disinfectant solution with an effective chlorine concentration of 5-10 g/l [43], soak a towel in the bag with the previously mentioned disinfectant solution, cover the vomitus with the towel for 30-60 min; (4) pick up the towel covering the vomitus and place it into a yellow garbage bag for medical waste, and disinfect the gloves with 5% Iodophor disinfection cotton [44]; (5) remove the outer gloves and the protective equipment, and then remove the next pair of gloves and thoroughly clean the hands.…”
Section: Discussionmentioning
confidence: 99%